Setting the record straight: a re-examination of ants (Hymenoptera: Formicidae) from Cyprus deposited at the Museum of Zoology of Athens - Demetriou, Jakovos; Georgiadis, Christos; Ralli, Vasiliki; Salata, Sebastian; Borowiec, Lech (Zootaxa, 2024)
Situated in the Eastern Mediterranean, the island of Cyprus is a biodiversity hotspot hosting an important number of endemic species. In recent years, its myrmecofauna has been increasingly enriched with the detection of both new alien and native species as well as the description of new endemic taxa. Nevertheless, earlier reports of dubious taxa remaining in scientific literature constitute an impediment towards the study of the island’s biodiversity. This article summarizes the results of re-examination of a collection of ants deposited in the Museum of Zoology of the University of Athens, which was a source of some faunistic records recently published as a conference poster. Specimens have been re-identified, and their metadata have been digitalised, supplementing our knowledge of the species’ distribution and correcting previous misidentifications. Tapinoma festae Emery, 1925, Tapinoma glabrella (Nylander, 1849) (Dolichoderinae), Plagiolepis perperamus Salata, Borowiec & Radchenko, 2018, Plagiolepis xene Stärcke, 1936 (Formicinae), Crematogaster lorteti Forel, 1910, and Tetramorium indocile Santschi, 1927 (Myrmicinae) are reported for the first time for the island. Adiitionally, a new distributional record is also provided for Camponotus cf. vitiosus, an enigmatic alien species on Cyprus. Lastly, a number of dubious records are removed from the checklist of Cypriot ants with notes on further taxa that could be removed in the future.